1985
DOI: 10.1159/000145933
|View full text |Cite
|
Sign up to set email alerts
|

Bone Mineral Content of Limb Bones of Male Weanling Rats Subjected to 30 and 60 Days of Simulated Increases in Body Weight

Abstract: The purpose of this study was to subject groups of male rats each to a specific 10% simulated increase in body weight, ranging from 1.1 to 2.0 g. Constant centrifugation was employed. After 30 and 60 days, rats were sacrificed and perfused with 10% BNF. The humerus, radius, ulna, femur, and tibia were removed, cleared of all soft tissues, weighed, decalcified with EDTA, and reweighed. Bone mineral content (BMC) was determined using the formula: [(Wu – Wd) ÷ Wu] × 100. Tukey’s m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

1986
1986
2006
2006

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 5 publications
1
13
0
Order By: Relevance
“…Many studies have shown the effects of a hypergravity environment on bone of animals (Rosenfeld et al , 1973;Fosse et al , 1974;Jaekel et al, 1977;Smith, 1977;Gazit, 1980;Pace et al, 1985;Simon et at., 1985;Wunder et al, 1987). In addition, ultrastructural reports have dealt with the problem on the influence of a hypergravity environment on the parathyroid gland (Sannes and Hayes, 1975; Shoumura et at., 1988a, 1989a, 1989b; Isono et al, 1990; Shoumura et al, 1990Shoumura et al, , 1991aShoumura et al, , 1991bShoumura et al, , 1992aShoumura et al, , 1992bShoumura et al, , 1992c.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown the effects of a hypergravity environment on bone of animals (Rosenfeld et al , 1973;Fosse et al , 1974;Jaekel et al, 1977;Smith, 1977;Gazit, 1980;Pace et al, 1985;Simon et at., 1985;Wunder et al, 1987). In addition, ultrastructural reports have dealt with the problem on the influence of a hypergravity environment on the parathyroid gland (Sannes and Hayes, 1975; Shoumura et at., 1988a, 1989a, 1989b; Isono et al, 1990; Shoumura et al, 1990Shoumura et al, , 1991aShoumura et al, , 1991bShoumura et al, , 1992aShoumura et al, , 1992bShoumura et al, , 1992c.…”
Section: Discussionmentioning
confidence: 99%
“…1980;Pace et al. 1985;Simon et al. 1985;W underet al, 1987], and an increase in the bone density of animals exposed to hyper gravity has been documented [Amtmann and Oyama, this study was supported by a research grant from the Ministry of Hducation of Japan.…”
Section: Introductionmentioning
confidence: 98%
“…Many studies have shown the effects of a hypergravity environment on bone [1][2][3][4][5][6][7][8][9]. and morphological investiga tions have dealt with the problem concerning the effects of a hypergravity environment on the parathyroid gland [10][11][12][13][14][15][16][17], Many reporters have examined the ultrastructure of the parathyroid glands of mammalian fetuses and chick embryos under experimental conditions [18][19][20][21] as well as under normal conditions [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%